Imaging of the intrinsic muscles of the hand – Part II: Pathological aspects on high-resolution ultrasound and 3T MRI - Bouredoucen, Hicham; Boudabbous, Sana; Poletti, Pierre-Alexandre; Taihi, Lokmane (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2026)
There are numerous pathologies of the intrinsic muscles of the hand (IMH). Muscle denervation syndromes of the hand are common in pathologies of the median nerve (MN) and ulnar nerve (UN). They occur following carpal tunnel syndrome, Guyon’s canal syndrome, traumatic, tumoral, inflammatory, or proximal nerve lesions due to upper cervical radiculopathy, or brachial plexus lesions. Myositis of the IMH occurs in various contexts. Traumatic muscle injuries of the hand are rare. Some are characteristic, such as lesions of the third interosseous muscle (IOM) or lesions of the lumbrical muscles (LM) in climbers. Saddle syndrome is due to adhesions of the lumbrical-interosseous intermuscular junctions. It is very often overlooked. In rheumatoid arthritis, tendon tenosynovitis of the IOM is frequently encountered. Enhancement of the LM may be an early imaging marker of the disease. Multiple tumor or pseudotumoral masses can develop within or around IMH. All of these pathologies can be accurately assessed using high-resolution dynamic ultrasound (US) and high-field 3T magnetic resonance imaging (MRI).This educational review presents the aspects of the various IMH pathologies on high-resolution US and high-field 3T MRI.There are numerous IMH pathologies. A radiologist’s knowledge and assessment of these various pathologies allows clinicians and surgeons to make an early and accurate diagnosis and choose the most appropriate treatment.
Keywords: Intrinsic muscles of the hand; Muscular denervation; Carpal Tunnel Syndrome; Guyon’s Canal Syndrome; Myositis; MRI imaging